Innovative SCM Practices Driving Growth: A Case Study of Mixue's Pauh Branch in Padang City - Suprapto; Azmen Kahar (Pt. Threeple Herphi Educate, 2024)
This study investigates the implementation of Supply Chain Management (SCM) and the advantages of the franchise business model at Mixue, a culinary brand specializing in sweet dishes, particularly in its Pauh branch. The objective is to evaluate how efficient SCM practices and comprehensive support from the franchisor, including training and the provision of high-quality raw materials, have contributed to Mixue's rapid expansion in Indonesia. A thorough literature review was conducted to identify the key factors driving Mixue's success. The findings reveal that Mixue's SCM system ensures the seamless distribution of raw materials across all outlets, maintaining consistent product quality. Additionally, continuous operational support from the parent company offers attractive business opportunities for franchisees. The study concludes that the integration of an effective SCM system with a robust franchise model has enabled Mixue to create a profitable business ecosystem, establishing it as a major player in Indonesia's culinary industry